Paths to Victory - Paul, Christopher; Clarke, Colin P.; Grill, Beth; Dunigan, Molly (RAND Corporation, 2023)
Building on a 2010 RAND study of the 30 insurgencies begun and completed between 1978 and 2008, this study added 41 new cases to the data set, allowing comparisons across all 71 insurgencies begun and completed worldwide since World War II to distill the paths to victory. With many more cases to compare, the study was able to more rigorously test the previous findings and address several critical questions that the earlier study could not.